1994
DOI: 10.1111/j.1475-2743.1994.tb00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Maize growth responses to deep tillage, straw mulching and farmyard manure in coarse textured soils of N.W. India

Abstract: The effects of deep tillage, straw mulching and farmyard manure on maize growth in loamy sand and sandy loam soils were studied in experiments lasting three years. Treatments included all combinations of conventional tillage (10 cm deep) and deep tillage (35-40 cm deep), two farmyard manure rates (0 and 15 t/ha) and two mulch rates (0 and 6 t/ha), replicated three times in a randomized H E~K I E , A.T.P. & ROTIIA, F.J.P. 1986. Effect of deep tillage and controlled traffic on root growth, water use efficiency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
42
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 10 publications
8
42
0
1
Order By: Relevance
“…Abayomi and Adedoyin (2004) also found that application of higher dose of N significantly reduces time to tassels and silk emergence. Gajri et al (1994) also reported that phenological parameters of maize were significantly affected by the amount of N fertilization and deep tillage. The subsoil compaction advanced the dough stage by about 6 days and 4 days during the year 2012 and 2013, respectively ( Table 2), than that in no subsoil compaction treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Abayomi and Adedoyin (2004) also found that application of higher dose of N significantly reduces time to tassels and silk emergence. Gajri et al (1994) also reported that phenological parameters of maize were significantly affected by the amount of N fertilization and deep tillage. The subsoil compaction advanced the dough stage by about 6 days and 4 days during the year 2012 and 2013, respectively ( Table 2), than that in no subsoil compaction treatment.…”
Section: Resultsmentioning
confidence: 99%
“…This is a newly evolving field of science and technology using plants to clean-up polluted soils, waters, or air (5,6), and is a particularly important because contaminated soils are often used for vegetable production. A technique that has strongly boosted agricultural output in the last few years is the use of plastic covers over the soil surface which significantly influences the root zone temperatures (7), depending on the composition of the plastic as well as its efficiency in absorbing light (8,9). Rootzone temperature is a key factor in altering ion accumulation (10).…”
Section: Introductionmentioning
confidence: 99%
“…While a greater likelihood of yield loss might exist in fine-textured soils which generally developed lower water potentials and water depletion zones around the roots (Shein and Pachepsky, 1995), high soil temperature during early part of the growing season in medium-to coarse-textured soils remained a constraint to improve soybean yield in the IndoGangetic plains of South Asia (Arora et al, 2011). The application of mulch has been shown to improve yield by reducing plant sensitivity to water and temperature stress (but see Chen et al (2007)), although the extent of the improvement might vary with location (e.g., upland, lowland) (Zhang et al, 2009), type and thickness of mulch (Ramakrishna et al, 2006), as well as soil texture (Gajri et al, 1994).…”
mentioning
confidence: 99%